2013
DOI: 10.1007/s00590-013-1361-4
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic and surgical features in the management of patients with haemophilia

Abstract: Haemophilia is a hereditary disease due to a defect of the X chromosome, which determines a faulty production of coagulation factor VIII in haemophilia A (85% of cases) and factor IX in haemophilia B. Three degrees of severity can be distinguished: low, with a deficient factor concentration greater than 5% of normal values, medium, with a concentration between 1 and 5%, and severe, comprising more than half of haemophilia cases, with a concentration of factor VIII or factor IX under 1% of normal. The evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The patients who underwent hip and elbow replacement had no perioperative wound complications, which is in line with reports in other countries . The above data show that with full perioperative preparation, joint replacement surgery is safe and effective in patients with hemophilia.…”
Section: Discussionsupporting
confidence: 88%
“…The patients who underwent hip and elbow replacement had no perioperative wound complications, which is in line with reports in other countries . The above data show that with full perioperative preparation, joint replacement surgery is safe and effective in patients with hemophilia.…”
Section: Discussionsupporting
confidence: 88%
“…However, recent data demonstrated that good surgical results are achievable over a range of procedures when there is appropriate careful preoperative planning, appropriate replacement/ substitution therapy, and multidisciplinary team management. [501][502][503][504][505][506] Although surgery is a highly demanding intervention in patients with severe IBDs, especially in low-resource countries, 507 it often represents a life or limb-saving and quality of life-improving measure, which has to be taken.…”
Section: General Perioperative Management Recommendationsmentioning
confidence: 99%
“…Length of stay in hospital for perioperative management is not only affected by clinical characteristics (eg surgery complexity, existence of treatment complications) but can also be affected by local protocols arising from funding restrictions; ultimately, this encouragespreoperative factor dosing in outpatients and early discharge for outpatient dosing of additional doses. The appropriate use of coagulation factor products combined with regular assessments at a haemophilia (or bleeding‐disorder) comprehensive care centre, supplemented with symptomatic support (eg physiotherapy around orthopaedic surgery), was shown to assist the majority of patients in recovering from surgery …”
Section: Resultsmentioning
confidence: 99%
“…Low incidences of postoperative bleeding and other complications were reported in studies from Romania, France and the United Kingdom. 4,24,25 These studies highlighted the importance of timely monitoring of factor levels and close collaboration within the MDT during the perioperative period.…”
Section: Monitoring Factor Levels and Other Laboratory Issuesmentioning
confidence: 99%